Deuterium and helium ion irradiation of nanograined tungsten and tungsten–titanium alloys. (December 2019) - Buzi, L.; Yeh, M.; Yeh, Y-W.; Donaldson, O.K.; Patino, M.I.; Trelewicz, J.R.; Yao, N.; Doerner, R.; Koel, B.E.
Highlights: Engineered W and W–20Ti alloy (W alloy with 20 at.% Ti) were exposed to D and he plasmas and gas retention as well as surface modifications were evaluated. Nanograined W was observed to have superior performance (smaller D -induced blisters and less developed He-induced fuzz) compared to larger grain W. Abstract: Tungsten (W), a primary candidate for the plasma-facing components of nuclear fusion reactors (e.g. the divertor region in ITER) is susceptible to cracks, blisters, bubbles, and other morphological changes when irradiated with energetic particles. This work investigated two new materials, nanograined W and a nanograined W–Ti alloy, for potential use as plasma-facing materials. Their retention properties and morphological changes after exposure to deuterium (D) and helium (He) plasma at 50 eV and surface temperatures of 500 and 1000 K were analyzed. Nanograined W was found to have smaller blisters and be less prone to fuzz formation than commonly-utilized micro-grain polycrystalline W. Additionally, the nanograined W–Ti alloy exhibited a lower concentration of blisters on its surface than pure W, including nanograined W.